Perspective—Multinary Oxide Semiconductors for Solar Fuels Generation: Closing the Performance Gap between Theory and Practice. (1st May 2022) - O'Donnell, Shaun; Vali, Abbas; Rawat, Abhishek; Maggard, Paul A.; Huda, Muhammad N.; Rajeshwar, Krishnan
Abstract : This Perspective addresses the current state-of-the-art with the development of multinary oxides—a family of compounds that has long interested Prof. John B. Goodenough. Specifically, here we focus on their use as photoelectrodes for solar fuels generation. Using optical data and assuming an idealized 100% incident photon-to-electron conversion efficiency, it is possible to project the maximum short circuit photocurrent efficiency to be expected for a given oxide semiconductor. The performance gap between this theoretical value and that realized experimentally, is shown to be sizable for all but a couple of candidates. The technical issues underlying this gap and strategies for closing it are presented below.